Biodegradable oesophageal stents for refractory benign disease: a case series. (13th March 2011) - Hazeldine, S; Wu, J; Law, R; Przemioslo, R
Abstract : Introduction: Benign oesophageal strictures that are refractory to dilatation are difficult to treat and may require the placement of an oesophageal stent. Biodegradable oesophageal stents (BDOS) are licensed for use in benign oesophageal strictures including achalasia. The biodegradable stent has advantages over metal stents as it negates the need for removal and has few reported local adverse events, the most common being stent migration. We report our experience of BDOS in patients with benign oesophageal strictures refractory to repeated dilatation. Methods: Patients were considered to have refractory benign oesophageal strictures if histology was negative for malignancy and had undergone at least 3 previous balloon dilatation procedures. Ella BD Polydioxanone stents (UK Medical) were placed under endoscopic and fluoroscopic visualisation with conscious sedation. Stent position and function was checked the following day with a barium swallow. Patients were then followed up clinically, recording dysphagia symptoms, stent migration and complications. Results: Four patients were identified with refractory benign oesophageal strictures. Mean age 68 (57–87), 3 male and 1 female. Stricture aetiology; 2 achalasia, 1 peptic and 1 postradiotherapy. Follow-up period poststent insertion ranged from 1 to 7 months. On initial inspection all 4 stents were placed correctly. Follow-up barium swallow on day 1 showed one stent had migrated distally (achalasia), this was replaced in the correct position endoscopically. At day 7, dysphagia was not relieved in 1 of 4 patients (achalasia), despite adequate stent patency. At 1 month only 1 of 4 patients had symptom relief (peptic stricture) and was still symptom free at 7 months. Complications included severe odynophagia requiring stent removal (postradiation), food bolus obstruction and aspiration pneumonia (achalasia). Conclusion: We have experienced variable success in our use of biodegradable stents. In our experience BDOS did not provide significant benefit in those patients with achalasia especially if it was longstanding and there was poor oesophageal motility. Only one patient (peptic stricture) had a prolonged response to dysphagia. Larger case series are required to ascertain the role of BDOS in patients with refractory benign oesophageal strictures.